2014
DOI: 10.1063/1.4863933
|View full text |Cite
|
Sign up to set email alerts
|

MgO-based magnetic tunnel junction sensors array for non-destructive testing applications

Abstract: A MgO-based magnetic tunnel junction (MTJ) sensor including 72 MTJs in series with 50 × 50 μm2 was successfully microfabricated. Due to a two-step annealing strategy, a linear transfer curve was obtained. The tunneling magnetoresistance (TMR) value is as high as 159% and the sensitivity reaches 2.9%/Oe. The field detectivity exhibits the lowest value at 1 V bias current, attaining 1.76 nT/Hz0.5 and 170 pT/Hz0.5 for 10 Hz and 1 kHz, respectively. The results show that the sensor could be applied in non-destruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…One could therefore conclude that the best sensor configuration will be the one that produces a higher signal variation and therefore a sensor with N = 60 rows (corresponding to a height of 3 mm) would be the best solution. However, by adding rows of MTJ, the noise of the sensor will also be added with a rate of √ N compromising the SNR [12].…”
Section: Probe Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…One could therefore conclude that the best sensor configuration will be the one that produces a higher signal variation and therefore a sensor with N = 60 rows (corresponding to a height of 3 mm) would be the best solution. However, by adding rows of MTJ, the noise of the sensor will also be added with a rate of √ N compromising the SNR [12].…”
Section: Probe Optimizationmentioning
confidence: 99%
“…These sensors also show much higher sensitivities to magnetic fields when compared with AMR and GMR sensors [11], which facilitate the detection of very low-magnetic field variation that are often observed in NDT applications. Finally, it was also demonstrated that a sensor including a series of MTJ elements show improved SNRs under a homogeneous magnetic field [12]. Nevertheless, in NDT applications based on eddy currents and in particular when detecting surface defects, the magnetic field sensed by each MTJ elements of a series can be very inhomogeneous.…”
Section: Introductionmentioning
confidence: 95%
“…CoFeB/MgO/CoFeB-MTJ data obtained at operation point. Data marked with i from references [119,123,124] and ii is unpublished data from INESC-MN; * from reference [90]; + from reference [85]; & from reference [42]; α from reference [118]; β from reference [125]; δ is unpublished data from INESC-MN; σ from reference [41]; γ from reference [83]. Comparison between single sensors (solid shapes) and sensors with integrated MFCs (half-right shapes).…”
Section: Ptesla Detectivity Levelsmentioning
confidence: 99%
“…Comparison between single sensors (solid shapes) and sensors with integrated MFCs (half-right shapes). Square shapes represent data for micrometric structures from reference [41], either individual circular sensors (radius of 10, 28 and 36 µm) or series of 952 square sensors (50 × 50 µm 2 each); pentagonal shape from reference [83] measured at 10 Hz; left-triangle shape from reference [125]; right triangle shape from reference [118] whereas star shape represents data for nanometric circular MTJ pillars (radius 200 nm) from reference [42]. Simple sensing layer data from reference [90] (upward triangle) and [85] (downward triangle), and SPM-like sensing layer results from reference [92].…”
Section: Ptesla Detectivity Levelsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Applications of MTJs have extended beyond read heads in hard disk drives and MRAMs. MTJ sensors have been used for medical and biological devices, 20 high frequency oscillators, 24 non-destructive testing, 25 current sensors, 26 and ultra-low noise sensors. 27 MTJ sensors due to its high sensitivity and thermal performance have becoming an enabling technology in many areas of science and engineering.…”
mentioning
confidence: 99%